2022
DOI: 10.3390/foods11040587
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Functional Modifications of Hemp Protein Concentrate by the Application of Ultrasonication and pH Shifting Treatments

Abstract: According to the Food and Agriculture Organization (FAO), protein demand is expected to increase globally by around 40% by 2030 as a response to the world’s population growth. Due to their clean label, vegan or vegetarian based applications, nutritional value, and cost-efficient properties, plant-based proteins have been widely studied. However, most of the alternatives currently found in the market have some challenges because of their poor solubility, emulsifying, gelling, and foaming attributes. Hemp seed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Regarding −SH content, hemp protein had a −SH content of 34.85 μmol/g, which is significantly higher than those of its two plant-based peers (19.83 μmol/g for soy and 13.07 μmol/g for pea) but is lower than those of the two animal-based counterparts (37.41 μmol/g for whey and 48.54 μmol/g for egg albumin) (Table ). These results are in the range of −SH contents presented in previous studies: 32.82 μmol/g for hemp, 50.53 μmol/g for egg white, 39.84 μmol/g for whey, 18.05 μmol/g for soy, and 12.60 μmol/g for pea, respectively. , Some variations could be attributed to the protein sources. The higher −SH content in hemp protein is related to higher amounts of cysteine, which has an active −SH group, compared to soy or pea.…”
Section: Resultssupporting
confidence: 67%
“…Regarding −SH content, hemp protein had a −SH content of 34.85 μmol/g, which is significantly higher than those of its two plant-based peers (19.83 μmol/g for soy and 13.07 μmol/g for pea) but is lower than those of the two animal-based counterparts (37.41 μmol/g for whey and 48.54 μmol/g for egg albumin) (Table ). These results are in the range of −SH contents presented in previous studies: 32.82 μmol/g for hemp, 50.53 μmol/g for egg white, 39.84 μmol/g for whey, 18.05 μmol/g for soy, and 12.60 μmol/g for pea, respectively. , Some variations could be attributed to the protein sources. The higher −SH content in hemp protein is related to higher amounts of cysteine, which has an active −SH group, compared to soy or pea.…”
Section: Resultssupporting
confidence: 67%
“…As a result of this phenomena, cavitational forces are developed, which are responsible for smaller particle size of the medium and creating high shear forces (Zhao et al, 2022). Numerous authors have shown that ultrasound technology can modify the functional, structural, thermal, and rheological behavior of protein foods by altering their secondary characteristics (Hertzler et al, 2020; Kahraman et al, 2022; Kaur et al, 2021; Lafarga et al, 2018; Lo et al, 2022; Sidhu et al, 2019; Thalía Flores‐Jiménez et al, 2022; Wang et al, 2017). However, no information is available on the extraction and modification in the physico‐chemical, thermal, and rheological properties of sunnhemp proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been scientifically proved that a lower digestibility of plant based proteins, such as grains or legumes including hemp are strictly correlated with the presence of antinutritional factors, such as phytic acid and trypsin inhibitors identified in hemp seed. [16] [17] In comparison with other plant based sources of protein, hemp has a similar PDCAAS score with black and pinto beans, as well as lentils [18].…”
Section: Evaluating Hemp and Rapeseed Protein Qualitymentioning
confidence: 99%